The development of a web-based information tool for cross-border prevention and control of Methicillin Resistant Staphylococcus aureus - Verhoeven, Fenne; Hendrix, Ron M.G.; Daniels-Haardt, Inka; Friedrich, Alexander W.; Steehouder, Michael F.; van Gemert-Pijnen, Julia E.W.C. (International Journal of Infection Control, 2008)
Increased international trade in health services and particularly patients and health care givers crossing European borders can have an important role in the rapid spread of health care associated infections, such as methicillin-resistant Staphylococcus aureus (MRSA). Therefore, the project EUREGIO MRSA-net Twente/Münsterland, in which local health care providers exchange knowledge and technology, aims to equalize quality criteria to reduce cross-border MRSA spread. Since it launch in 2005, the project has now established a cross-border infrastructure of which a web-based MRSA tool is part (www.mrsa-net.nl). This web-based tool should facilitate health care workers with acceptable, applicable, user-friendly information and evidence-based guidelines that enhance the decision making process and enable them to deliver safe health care. We applied a user-centered design approach to develop this web-based tool. The approach included a pre-design phase with a deep qualitative analysis of Dutch and German health care workers’ needs and their current activity and work habits, to ensure that the web-based tool will be successfully integrated in their daily work practice. In the design phase, five different methods were used to create a web-based tool completely based on user needs. For instance, Scenario Testing and Card Sorting provided us with insights in the thinking and acting of health care workers, which helped us to fully adapt the tool to the user needs. Moreover, we found that involving users is important to create ownership and to foster the applicability of the tool. The involvement of key players and users is important to ensure that the tool’s content is in accordance with existing guidelines. By providing health care workers with our tool, we aspire to enhance cross-border patient safety.